Effect of clamping force on distortion of the optical surface of monochromators during assembly. (22nd April 2022) - Bainbridge, Eleanor Victoria; Griffiths, Jonathan David; Clunan, Jessica; Docker, Peter
Abstract : This work demonstrates the effects of clamping force on the optical surface of a monochromator silicon crystal through the use of finite‐element analysis. Abstract : As Diamond Light Source embraces the move towards becoming a fourth‐generation light source its optics will be required to perform under increasingly demanding conditions. Foremost amongst these conditions will be the increasing power densities the optics are subjected to and the reducing real estate they have to perform in. With these new challenges comes the need for greater understanding of how optics are assembled and how consistently the activity is carried out. In this paper, the effect of bolt pretension during assembly of monochromators on distortion of the optical surface is investigated through numerical simulation. The results reveal skewed convex distortion of the optical surface in the meridional direction when uneven clamping force is applied, highlighting the importance of taking the potential for distortion of the optical surface due to clamping force into consideration.